An Implementation of a Strategy for IT Projects Portfolio Management in the Public Sector in accordance with the MPS Reference Model for Software using Action Research - de Medeiros, P. A.; de Moura, Hermano P.; Oliveira, Sandro R. B. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Projects are undertaken at all organizational levels, both in the public and private environments, and managing them is not a trivial activity, involving the application of a large amount of knowledge, skills, tools and techniques, in order to better meet requirements agreed between the parties involved. However, in addition to the need of managing projects, one of the major challenges within organizations is how they define which projects are priorities or what is the best combination of projects to achieve strategic business objectives. In this scenario, Project Portfolio Management (PPM) gains importance, becoming the area or process responsible, not only for a specific project, but also for activities that involve the management of an organization's entire portfolio of projects. This type of activity is vital because it has a strong impact on the direction of investments and on the use of certain business opportunities. Nevertheless, researches such as those carried out by the Tribunal de Contas da União, presented a number of concerns regarding the adoption of good practices, present in the PPM, in the area of Information Technology (IT). The purpose of this research was to define, execute and evaluate a strategy for the implementation of the IT Projects Portfolio Management in the public environment, in light of the MPS Reference Model for Software (MR-MPS-SW:2016), in order to improve the practices of a public software development organization and generate knowledge. An Action Research, methodological approach of applied and interventionist nature, which structured the generation of knowledge presented in this work, contributing both to theory and practice, conducted the study. The analysis of the strategy was carried out from the data collection, made by the application of a research questionnaire with the people who executed the PPM strategy.